EFFECT OF BIOACTIVE CHITOSAN-CONTAINING COMPOUNDS ON THE ACTIVITY OF DIGESTIVE ENZYMES (AMYLASE, LIPASE, PROTEASE) - Rakhmonov Farkhod Kholbayevich; Furkatova Sabrina Farmonovna (Modern American Journals, 2026)
This research investigates the modulatory effects of chitosan-based bioactive compounds on three key digestive enzymes—amylase, lipase, and protease. Due to its sorptive capacity, muco-protective behavior, and microbiota-regulating properties, chitosan contributes substantially to optimizing gastrointestinal biochemical conditions. Experimental findings show that a dietary inclusion of 100 mg/kg chitosan markedly improves the hydrolysis of carbohydrates, lipids, and proteins. The demonstrated enhancements suggest that chitosan can serve as a functional feed additive and an effective physiological regulator of digestive enzyme activity.
Keywords: Chitosan, digestive enzymes, intestinal microbiota, pH regulation, amylase, lipase, protease, bioactive compounds.